Evaluating user satisfaction of Sistem Pengurusan Inventori Armada Versi 2 (SPIA V2) in Royal Malaysian Navy (RMN) Fleet Supply Depot (FSD) / Wan Mohd 'Aizat Wan Ariffin - Wan Ariffin, Wan Mohd 'Aizat (2015)
Sistem Pengurusan Inventori Armada Versi 2 (SPIA V2) is a specially design system for Fleet Supply Depot (FSD) to manage all data and information regarding their logistics, demand and supplies, spare parts purchasing and storage, equipment management and personnel of Fleet Supply Depot (FSD). However, the system has only been evaluated once during acceptance of SPIA V2 in 2008 and only focused on execution of system. There is no involvement from users during the evaluation therefore any views or recommendations from them have not been taken into consideration. Other than that, change of personnel, lack of budget for continuous training and minimal transfer of knowledge among users has contribute to ongoing complaint from users towards the system. Until 2013, 112 problems has been recorded and identified about system and data error in SPIA V2. Thus, a user evaluation has been recommended by the Commanding Officer (CO) to identify what are the problems and determine how effective, efficient and comprehensive SPIA V2 from the perspective among FSD personnel. For study purposes, Demand Management Module will be evaluated based on 8 elements and focused more on user satisfaction towards information provided by SPIA V2. An enhanced End User Computing Model (EUCS) developed through discussion with officers from each department to form up set of questions and has been delivered through interviews and questionnaires. All quantitative and qualitative information are collected and analyze to get a better view on user satisfaction towards the system. Overall, a result has shown that SPIA V2 is still effective and most elements have met user satisfaction but need improvement in certain areas.